Early Mapping of Student Science Literacy: A Preliminary Study for Tidal Flood Mitigation Learning Innovation Based on Deep Learning and Local Wisdom - Azimatul Khusniah; Andin Irsadi; Sudarmin Sudarmin; Novi Ratna Dewi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to provide an initial quantitative mapping of coastal students’ science literacy related to tidal flood mitigation, addressing the limited contextual understanding of disaster adaptation in schools. Using a quantitative descriptive survey design, the study involved 360 students from three coastal vocational high schools selected through proportional stratified random sampling. Data were collected through a PISA-based science literacy test and disaster mitigation perception questionnaires, then analyzed using descriptive statistics, One-Way ANOVA, and Pearson correlation tests. The findings showed that students’ overall science literacy was at a moderate level (mean = 68.61). Students demonstrated relatively good data interpretation skills (mean = 76.83), while their ability to explain natural phenomena scientifically remained lower (mean = 62.15). The ANOVA test indicated no significant difference in science literacy among the three schools (p = 0.946). In addition, a very strong positive correlation (r = 0.82) was observed between science literacy and students’ perceptions of disaster resilience. The novelty of this study lies in its integration of coastal disaster literacy mapping with a deep-learning pedagogical approach grounded in local wisdom. These findings provide empirical evidence that science literacy in coastal schools remains insufficiently connected to students’ environmental realities, highlighting the importance of contextual and culturally responsive science learning for disaster mitigation education.